Nonselective conduction in a mutated NaK channel with three cation-binding sites. - Furini, S; Domene, M (2012)
The NaK channel is a cation-selective protein with similar permeability for K(+) and Na(+) ions. Crystallographic structures are available for the wild-type and mutated NaK channels with different numbers of cation-binding sites. We have performed a comparison between the potentials of mean force governing the translocation of K(+) ions and mixtures of one Na(+) and three K(+) ions in a mutated NaK channel with only three cation-binding sites (NaK-CNG). Since NaK-CNG is not selective for K(+) over Na(+), analysis of its multi-ion potential energy surfaces can provide clues about how selectivity originates. Comparison of the potentials of mean force of NaK-CNG and K(+)-selective channels yields observations that strongly suggest that the number of contiguous ion binding sites in a single-file mechanism is the key determinant of the channel's selectivity properties, as already proposed by experimental studies. We conclude that the presence of four binding sites in K(+)-selective channels is essential for highly selective and efficient permeation of K(+) ions, and that a key difference between K(+)-selective and nonselective channels is the absence/presence of a binding site for Na(+) ions at the boundary between S2 and S3 in the context of multi-ion permeation events.